Hip and groin pain in male field hockey players: Prevalence, incidence and associations with patient reported outcome scores and hip muscle strength - Beddows, T. P. A.; Weir, A.; Agricola, R.; Tak, I. J. R.; Piscaer, T. M.; Verhaar, J. A. N.; van Klij, P. (Physical Therapy in Sport, 2023)
Objectives: Investigate point prevalence (second half season 2018-2019) and incidence (season 2017-2018 and first half season 2018-2019) of non-time-loss and time-loss hip/groin pain in male field hockey players. Secondary aims were to study associations between: current/previous hip/groin pain and hip muscle strength, patient reported outcome measures (PROM) and hip muscle strength, and previous hip/groin pain and PROMs. Additionally we studied normal values for the PROMs (Hip and Groin Outcome Score (HAGOS)). Design: Cross-sectional study. Setting: Testing at field hockey clubs. Participants: 100 male field hockey players (elite, sub-elite and amateur). Main outcome measures: Point prevalence and incidence of hip/groin pain, strength: eccentric adduction and abduction, adductor squeeze, HAGOS. Results: Hip/groin pain point prevalence was 17% (time-loss: 6%) and incidence was 36% (time-loss: 12%). Presence of current or previous hip/groin and lower HAGOS-values were not associated with lower hip muscle strength. Previous hip/groin pain was associated with a significant lower HAGOS-values in all domains, except for the `participation in physical activities` domain. Conclusions: Hip/groin pain is common in field hockey. One fifth of players have hip/groin pain and one third had pain in the previous season. Previous hip/groin pain was associated with worse ongoing patient reported outcomes in most domains.